2013
DOI: 10.1007/s12160-013-9562-y
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Undergo Colonoscopy Screening Among Relatives of Colorectal Cancer Cases: a Theory-Based Model

Abstract: Future interventions to promote colonoscopy in this increased risk population should target the factors we identified as motivators. (ClinicalTrials.gov number NCT01274143).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…This result is consistent with a finding that increased apprehension about developing breast cancer is a modest but reliable predictor of increased likelihood to get screened (Hay, McCaul, & Magnan, 2006). Guided by the EPPM, another study examined cognitive, affective, social, and behavioural predictors of intention to undergo colonoscopy screening in individuals with a family history of CRC (Boonyasiriwat et al, 2014a). Relatives of colorectal cancer cases eligible for colonoscopy screening completed a survey assessing constructs from several theoretical frameworks.…”
Section: Discussionsupporting
confidence: 75%
“…This result is consistent with a finding that increased apprehension about developing breast cancer is a modest but reliable predictor of increased likelihood to get screened (Hay, McCaul, & Magnan, 2006). Guided by the EPPM, another study examined cognitive, affective, social, and behavioural predictors of intention to undergo colonoscopy screening in individuals with a family history of CRC (Boonyasiriwat et al, 2014a). Relatives of colorectal cancer cases eligible for colonoscopy screening completed a survey assessing constructs from several theoretical frameworks.…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with the literature, patient provider interaction emerged as a particularly important influence on screening in multivariable analyses 24, 25 . Insurance was an important predictor of screening among Latinos and African Americans.…”
Section: Discussionsupporting
confidence: 72%
“…One systematic review, 1 review article, and 10 original studies were identified for this question . A recent systematic review found that the most important predictors of screening adherence were having a physician recommendation (this increased the likelihood of screening 5‐ to 27‐fold) and having multiple affected family members (screening was 3.7 times more likely if more than 1 FDR was affected) .…”
Section: Resultsmentioning
confidence: 99%